Usability Evaluation of An Electronic Medication Administration Record (eMAR) Application - Guo, J.; Iribarren, S.; Kapsandoy, S.; Perri, S.; Staggers, N. (Applied Clinical Informatics, 2011)
Background: Electronic medication administration records (eMARs) have been widely used in recent years. However, formal usability evaluations are not yet available for these vendor applications, especially from the perspective of nurses, the largest group of eMAR users.Objective: To conduct a formal usability evaluation of an implemented eMAR.Methods: Four evaluators examined a commercial vendor eMAR using heuristic evaluation techniques. The evaluators defined seven tasks typical of eMAR use and independently evaluated the application. Consensus techniques were used to obtain 100% agreement of identified usability problems and severity ratings. Findings were reviewed with 5 clinical staff nurses and the Director of Clinical Informatics who verified findings with a small group of clinical nurses.Results: Evaluators found 60 usability problems categorized into 233 heuristic violations. Match, Error, and Visibility heuristics were the most frequently violated. Administer Medication and Order and Modify Medications tasks had the highest number of heuristic violations and usability problems rated as major or catastrophic.Conclusion: The high number of usability problems could impact the effectiveness, efficiency and satisfaction of nurses’ medication administration activities and may include concerns about patient safety. Usability is a joint responsibility between sites and vendors. We offer a call to action for usability evaluations at all sites and eMAR application redesign as necessary to improve the user experience and promote patient safety.
Keywords: Interfaces and usability; Human-computer interaction; Medication administration records; Electronic health record; Testing and evaluation